Effects of Treatment on IgE Responses against Parasite Allergen-Like Proteins and Immunity to Reinfection in Childhood Schistosome and Hookworm Coinfections - Pinot de Moira, Angela (American Society for Microbiology, 2013)
Naturally occurring human immunity to both schistosomiasis and hookworm infection has been associated with IgE responses against parasite allergen-like proteins. Since the two helminths frequently coinfect the same individuals, there is growing advocacy for their concurrent treatment. However, both helminths are known to exert strong immunomodulatory effects; therefore, coinfected individuals could have immune responses different from those characteristically seen in monoinfected individuals. In this study, we measured changes in IgE, IgG1, and IgG4 responses to schistosome and hookworm antigens, including the allergen-like proteins Schistosoma mansoni tegumental-allergen-like 1 protein (SmTAL1), SmTAL2, and Necator americanus Ancylostoma-secreted protein-2 (Na-ASP-2), following concurrent treatment of schoolchildren coinfected with Schistosoma mansoni and hookworm. Antibody responses to schistosome egg (soluble egg antigen and SmTAL2) or somatic adult hookworm (AHW) antigens either decreased after treatment or were unchanged, whereas those to schistosome worm antigens (soluble worm antigen and SmTAL1) increased. The observed different effects of treatment likely reflect the different modes of drug action and sites of infection for these two helminths. Importantly, there was no evidence that the simultaneous treatment of coinfected children with praziquantel and albendazole affected schistosome- and hookworm-specific humoral responses differently from those characteristic of populations in which only one organism is endemic; schistosome- and hookworm-specific responses were not associated, and there was no evidence for cross-regulation. Posttreatment increases in the levels of IgE to schistosome worm antigens were associated with lower Schistosoma mansoni reinfection intensity, while no associations between humoral responses to AHW antigen and protection from hookworm reinfection were observed in this sample of school-aged children.